Kajian Sistematis tentang Efektivitas Terapi Akupunktur terhadap Kasus Tinitus - Wijono Sukaputra Agussalim; Yelini Fan Hardi; Suminah Suminah; Fenny Yunita; Maya Septriana (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2023)
Background: Tinnitus is a frequently encountered health problem, suffered by about 10-15% of the people. The available treatment methods are variable and not fully satisfactory. Acupuncture is one of the therapy widely studied recently. Methods: This article reviews systematically publications about acupuncture therapy for tinnitus cases cited in the data base of PubMed and CNKI. Results: Tinnitus can be perceived from the aspects of western medicine and traditional Chinese medicine. Both aspects have similarity, i.e., that tinnitus is a symptom not a disease, that tinnitus could be caused by either internal or external causes. Studies have shown acupuncture therapy can be combined with and improve the effectiveness of conventional therapy for tinnitus. Conclusion: Effect of acupuncture therapy against neurogenic tinnitus has been reported from systematic review, meta-analysis, and controlled clinical trials. Combination of acupuncture therapy with conventional therapy brings better effectiveness compared to each therapy alone